El tránsito de la oralidad hacia la escritura en la experiencia jurídica del siglo XIII: ejemplo sajón e hipótesis castellana (parte primera) - Martínez Martínez, Faustino (Cuadernos de Historia del Derecho, 2007)
This first part studies the way followed by the European medieval law around the 12th and 13th centuries, from the orality of its customary manifestations to the writing, both inherited and of new formation, as much in Latin as in Roman languages. The diverse nature causes that could have inspired this change are examined, being all conducive to a greater legal security, and with it to the scientific knowledge, to finally project their effects in two well-known examples.